N6-Methyladenosine Modification and Its Regulation of Respiratory Viruses - Feng, Qianyu; Zhao, Hongwei; Xu, Lili; Xie, Zhengde (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is a ubiquitous RNA modification in eukaryotes, which plays an important role in the translocation, stabilization and translation of mRNA. Currently, it is known that deregulation of m6A modification is associated with diseases caused by pathogenic viruses. Studies on the role of m6A in virus-host interaction have shown that m6A has a broad regulatory role in the viral life cycle. Respiratory viruses are a kind of common pathogen that can impose a large burden of disease on young children and the elderly. Here, we review the effects of m6A modification on respiratory viral replication, life cycle, and immunity against viruses.